Impact of the Current US Preventive Services Task Force Recommendations for Cervical Cancer Screening in Young Women 21 to 29 Years Old - C. Paul Morris (2020)
© American Society for Clinical Pathology, 2020. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com. OBJECTIVES: In 2012, the US Preventive Services Task Force decreased the recommended frequency of cervical cytology screening to once every 3 years and recommended against testing women younger than 21 years regardless of sexual history. We evaluated the impact of this in 21 to 29-year-old women at a tertiary care academic medical center in 2011 and 2017. METHODS: We retrospectively analyzed Papanicolaou test results at two time points in 21- to 29-year-old women. RESULTS: There was a decrease in the number of high-grade lesions in 21- to 25-year-old women (odds ratio [OR], 0.36) from 2011 to 2017. Within the 26- to 29-year-old patient group, there was a trend toward a higher percentage of high-grade squamous intraepithelial lesion (HSIL) in 2017 compared to 2011 on cytology, which did not reach statistical significance (OR, 1.46). However, follow-up histologic specimens showed a higher percentage of HSIL in 2017 compared to 2011 in this age group (OR, 2.16). CONCLUSIONS: Our findings suggest that the cervical cancer screening guidelines introduced in 2012 have not had a detrimental impact on the outcomes of cervical cancer screening for 21- to 25-year-old women. However, we need to continue monitoring the effects of decreased screening in 26- to 29-year-old women.